2015
DOI: 10.1021/acs.jpclett.5b02309
|View full text |Cite
|
Sign up to set email alerts
|

Translation Symmetry Breakdown in Low-Dimensional Lattices of Pentagonal Rings

Abstract: The mechanism of translation symmetry breakdown in newly proposed low-dimensional carbon pentagon-constituted nanostructures (e.g., pentagraphene) with multiple sp(2)/sp(3) sublattices was studied by GGA DFT, DFTB, and model potential approaches. It was found that finite nanoclusters suffer strong uniform unit cell bending followed by breaking of crystalline lattice linear translation invariance caused by structural mechanical stress. It was shown that 2D sp(2)/sp(3) nanostructures are correlated transition st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 21 publications
1
26
0
1
Order By: Relevance
“…63 Sometimes, due to the breakdown of translational symmetry for low-dimensional materials with non-equivalent sublattices, phonon calculations in periodic boundary conditions cannot be used to prove whether or not a low-dimensional crystalline lattice is a local or global minimum. 64 The force constants also can be affected by phonon-magnetic coupling or strong electron correlations and soft modes may take place in magnetic and/or correlated low-dimensional systems. 65,66 The newly proposed h-CrN is an example of a strongly correlated low-dimensional magnetic material with non-equivalent sublattices.…”
Section: Resultsmentioning
confidence: 99%
“…63 Sometimes, due to the breakdown of translational symmetry for low-dimensional materials with non-equivalent sublattices, phonon calculations in periodic boundary conditions cannot be used to prove whether or not a low-dimensional crystalline lattice is a local or global minimum. 64 The force constants also can be affected by phonon-magnetic coupling or strong electron correlations and soft modes may take place in magnetic and/or correlated low-dimensional systems. 65,66 The newly proposed h-CrN is an example of a strongly correlated low-dimensional magnetic material with non-equivalent sublattices.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Zhang and coworkers [12] have reported the thermal and mechanical stability of pentagon-based carbon nanotubes (CNTs). Additionally, Avramov et al [25] have reported the binding energy per atom for (n, n) penta-graphene based carbon nanotubes (CNTs), confirming that the (7,7) penta-graphene based CNT is the most energetically stable structure. Pentagraphene is an attractive material for optoelectronic applications, because it is a semiconductor with a quasi-direct band gap.…”
Section: Introductionmentioning
confidence: 94%
“…Оказывается, однако, что термоактивированный поворот димеров С2 инициирует образование дефектных участков, которые не остаются локализованными, а быстро распространяются на весь образец, приводя к его полному разрушению [11]. Еще одним препятствием на пути изготовления пентаграфена может стать сильный изгиб образцов в процессе роста и даже их сворачивание в пентатрубки под действием механических напряжений, создаваемых двумя подрешетками димеров С2 [12].…”
Section: длина связи D(с2−с2unclassified